Trastuzumab induced radiation recall dermatitis: an interesting case - C., Anupama; H. V., Anuradha; Maka, Vinayak V. (International Journal of Basic & Clinical Pharmacology, 2018)
Radiation recall dermatitis (RRD) is the appearance of skin reactions in previously irradiated skin which is triggered by the administration of certain drugs. Surgery, chemotherapy, and radiotherapy are the mainstay of treatment in breast cancer. RRD induced by trastuzumab has been rarely reported in India. This is a case report of a 56-year-old woman presented to the medical oncology outpatient department of our hospital with breast lump, and she was diagnosed to have human epidermal growth factor receptor 2 (HER-2/neu) positive invasive ductal carcinoma of left breast of stage T2N3cM0. She was treated with neoadjuvant chemotherapy, and she underwent modified radical mastectomy with axillary lymph node dissection. The treating oncologist was planned to start on adjuvant chemotherapy with injection trastuzumab for every four weeks, for 15 cycles. Patient received first dose of injection trastuzumab (450 mg) intravenously in the right (contralateral) arm and developed painful, swollen, erythematous blisters, and maculopapular rashes following the sharp linear borders of her previous radiation fields. She was reviewed by the medical oncologist and diagnosed as a rare case of RRD and treated with topical betamethasone cream. Causality assessment for RRD to trastuzumab was done using Naranjo and WHO-UMC scale and found to be in the category of probable and probable/ likely respectively.